Spring Meetings Press Conference Opening Remarks by World Bank Group President David Malpass - Malpass, David (World Bank, Washington, DC, 2022)
These opening remarks were delivered by World Bank Group President David Malpass at Spring Meetings Press Conference on April 20, 2022. He said that we are facing COVID-19, inflation, and the war in Ukraine. He spoke about the World Bank Group has been acting fast in the face of the crises: first the Coronavirus (COVID-19) surge financing in over the last two years, which was one of the fastest and largest in our history; and now putting money into Ukraine and have moved quickly both to commitments and disbursements, including nearly 1.5 billion dollars that he announced in Poland last week. He mentioned that the World Bank Group is also working actively on climate, through its Climate Change Action Plan and the formation of Country Climate and Development Reports (CCDRs), which will identify the high priority items country by country, in their efforts to mitigate and to adapt to climate change. He was intrigued to see and welcomed India's moves the day before and that day to begin to sell from its stockpiles. He said that one of the solutions for the world is to recognize that markets are forward looking. He mentioned that the central banks can use tools that add to supply and that allow capital allocation to be improved. He concluded by saying that as interest rates rise, the debt pressures are mounting on developing countries, and we need to move urgently towards solutions.